2017
DOI: 10.1097/qai.0000000000001489
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Brain Atrophy Despite Persistent Viral Suppression in HIV Patients Older Than 60 Years

Abstract: Background Current HIV treatments are successful at suppressing plasma HIV RNA to undetectable levels for most adherent patients. Yet, emerging evidence suggests viral suppression will inadequately control inflammation and mitigate risk for progressive brain injury. We sought to quantify differences in longitudinal brain atrophy rates among older virally suppressed HIV-infected participants compared to that of healthy aging. Methods We examined longitudinal structural brain MRI atrophy rates employing region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 50 publications
9
41
1
Order By: Relevance
“…The presumably ongoing viral replication in the caudate nuclei, along with the associated neurotoxicity due to neuroinflammation (and/or neurotoxic side effects of antiretroviral agents), might result in growing neuronal injury in the caudate (Chang et al, ; Wang et al, ), which may eventually lead to detectable reduction in caudate volume and neurocognitive performance. Our hypothesis of this ongoing caudate injury model is also supported by findings from other studies: (a) Studies with postmortem brains and SIV models have suggested a high concentration of virus in the caudate nuclei (Kumar, Borodowsky, Fernandez, Gonzalez, & Kumar, ; Perez et al, ) and the basal ganglia in general, and the viral load in the caudate (along with the frontal cortex and the globus pallidus) correlates with neurocognitive impairment (Kumar et al, ); (b) Studies have found that the viral load in plasma and/or CSF correlates with caudate volume or neuronal injury in the caudate (Dewey et al, ; Krivine et al, ; Wang et al, ); (c) Studies have suggested a correlation between caudate volume and the estimated duration of HIV‐disease (Ances et al, ; Becker et al, ), implicating a gradual and ongoing decline in caudate volume after seroconversion, despite being on cART; (d) A recent longitudinal study with HIV+ older adults have found that not only the annualized rate of atrophy is higher in the caudate (0.74%) than any other brain regions in HIV (including the frontal lobe (0.48%) and the globus pallidus (0.73%)), but also the difference in the annualized rates of atrophy between HIV+ older adults and age‐matched controls is the largest in the caudate (ln [(1–0.0003)/(1–0.0074)] = ln (0.9997)−ln [0.9926] = 0.0071), followed by total cortical GM (0.0049) and the frontal lobe (0.0047), and is “twice” more than the globus pallidus (0.0034) (Clifford et al, ), suggesting that the caudate remains one of the most vulnerable and affected brain regions in HIV in the cART era; (e) Another longitudinal study also found that HIV+ adults with chronic infection have smaller caudate, putamen, and other subcortical regions than HIV+ adults with acute infection (Sanford et al, ), suggesting an ongoing neural injury to the caudate/striatum.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The presumably ongoing viral replication in the caudate nuclei, along with the associated neurotoxicity due to neuroinflammation (and/or neurotoxic side effects of antiretroviral agents), might result in growing neuronal injury in the caudate (Chang et al, ; Wang et al, ), which may eventually lead to detectable reduction in caudate volume and neurocognitive performance. Our hypothesis of this ongoing caudate injury model is also supported by findings from other studies: (a) Studies with postmortem brains and SIV models have suggested a high concentration of virus in the caudate nuclei (Kumar, Borodowsky, Fernandez, Gonzalez, & Kumar, ; Perez et al, ) and the basal ganglia in general, and the viral load in the caudate (along with the frontal cortex and the globus pallidus) correlates with neurocognitive impairment (Kumar et al, ); (b) Studies have found that the viral load in plasma and/or CSF correlates with caudate volume or neuronal injury in the caudate (Dewey et al, ; Krivine et al, ; Wang et al, ); (c) Studies have suggested a correlation between caudate volume and the estimated duration of HIV‐disease (Ances et al, ; Becker et al, ), implicating a gradual and ongoing decline in caudate volume after seroconversion, despite being on cART; (d) A recent longitudinal study with HIV+ older adults have found that not only the annualized rate of atrophy is higher in the caudate (0.74%) than any other brain regions in HIV (including the frontal lobe (0.48%) and the globus pallidus (0.73%)), but also the difference in the annualized rates of atrophy between HIV+ older adults and age‐matched controls is the largest in the caudate (ln [(1–0.0003)/(1–0.0074)] = ln (0.9997)−ln [0.9926] = 0.0071), followed by total cortical GM (0.0049) and the frontal lobe (0.0047), and is “twice” more than the globus pallidus (0.0034) (Clifford et al, ), suggesting that the caudate remains one of the most vulnerable and affected brain regions in HIV in the cART era; (e) Another longitudinal study also found that HIV+ adults with chronic infection have smaller caudate, putamen, and other subcortical regions than HIV+ adults with acute infection (Sanford et al, ), suggesting an ongoing neural injury to the caudate/striatum.…”
Section: Discussionsupporting
confidence: 85%
“…the frontal lobe (0.0047), and is "twice" more than the globus pallidus (0.0034) (Clifford et al, 2017), suggesting that the caudate remains one of the most vulnerable and affected brain regions in HIV in the cART era; (e) Another longitudinal study also found that HIV+ adults with chronic infection have smaller caudate, putamen, and other subcortical regions than HIV+ adults with acute infection (Sanford et al, 2018), suggesting an ongoing neural injury to the caudate/striatum.…”
Section: The Frontal/acc Atrophymentioning
confidence: 99%
“…The brain regions affected during untreated infection correspond with previous studies that examined people living with HIV. These studies reported volume reductions throughout the subcortical regions [2,3,[33][34][35][36] and cerebellum [37,38], and cortical thickness reductions in the frontal and temporal lobes, and cingulate cortex [2,3,17,39]. The data in aggregate add to the growing body of evidence that demonstrate the brain is not spared in early infection.…”
Section: Discussionmentioning
confidence: 77%
“…Although HIV and aging appear to contribute independently to heighten brain structural vulnerability (Ances et al, 2012 ), HIV may accelerate brain aging (Cysique et al, 2013 ; Cole et al, 2017 ). Consequently, despite persistent control of plasma viremia, older HIV infected patients demonstrate more rapid progressive brain compromise when compared to healthy aging (Clifford et al, 2017 ).…”
Section: In Vivo Neuroimaging Of Hiv and Comorbiditiesmentioning
confidence: 99%